Marketing Mix Sebagai Alasan Anggota Menabung Di KSP Artha Srikandi Banyuwangi - Rachmawati, Rizki (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Marketing strategy activities in terms of promotion, savingsproduct advantages and physical facilities will be successful ifsupported by good service quality with members. The service processthat is in accordance with the rules, fast and not convoluted will be ableto satisfy and please customers in saving the Cooperative. Thisresearch uses qualitative approach, ie approach based on data andprimary information meaningful in the end is trying to get the findingsof a theory that does contain the reality of truth. This research locus isKSP Artha Srikandi Banyuwangi has applied marketing mix, that isdetermination of saving product which is issued to attract members tosave, by picking up the ball, issuing savings model which gives manybenefits to member and giving guarantee of security of membermoney.Promotion done to attract members with interesting ads, alwaysfollow the exhibition and conduct social activities to be closer to thecommunity. Physical facilities owned adequate building, sara wideenough parking and safe, and a comfortable waiting room. Serviceprocess is done by serving accordingly rules and are not twisted.Keywords: Promotion, Product, Physical Means, Service Process